Interleukin 1 production by peripheral blood mononuclear cells from leprosy patients. - Watson, S (1984)
Quantitation of interleukin 1 production by adherent mononuclear cells from peripheral blood was performed in patients with tuberculoid and lepromatous forms of leprosy. Cells from patients with tuberculoid leprosy either secreted interleukin 1 spontaneously or produced amounts within the normal range in response to lipopolysaccharide stimulation. Conversely, stimulated cells from lepromatous patients failed to produce interleukin 1 in 5 of 13 (38.5%) cases.